EMU : Getting the end-game right - Begg, David; Giavazzi, Francesco; Von Hagen, Jurgen; Wyplosz, Charles (London : Centre for Economic Policy Research Washington : Brookings Institution Press [Distributor], 1997)
Written by a team of distinguished European academics, this report looks at the final stage of Europe's transition to a monetary union.
"October 1997" -
Includes bibliographic references
rpm 24/08/16
Loans
Keywords: Political Science; Public Administration; European Integration; European Monetary Union; Monetary union; Economic and Monetary union; Monetary policy; Europe